Response probability assessment of sexual enjoyment among Nigerian couples during COVID-19 lockdown (African Journal of Biomedical Research, 2021)
Regular pleasurable sex among couples is pivotal to nurturing a healthy marriage relationship, the lack of which has been associated with frequent misunderstandings, infidelity, gender-based violence and divorce in severe cases. The World Health Organization in January 2020 declared Coronavirus Disease (COVID-19) a global public health emergency. Countries all over the world declared lockdowns and formulated control measures to check the spread of the disease. Parents, children and relatives were locked down at home thereby eroding privacy among couples. This study assessed the response probability of sexual enjoyment/intimacy among Nigerian couples during COVID-19 lockdown.Convenience sampling using an online semi-structured questionnaire was employed to elicit information from 148 married Nigerian couples aged between 16 and 50+ years. Data was analyzed using SPSS version 23. Pearson Chi-Square (ꭓ2) was performed to determine associations between variables at 5% significance level (p-value ≤ 0.05). The assessment made use of response probabilities obtained by binary logistic regression modeling.Most respondents 81 (54.7%) were aged between 36-49 years; 75 (50.7%) were females, 73 (49.3%) were males. 109 (73.6%) were locked down in Nigeria. Majority 122 (82.4%) reported improvement in sexual intimacy; most 106 (71.6%) enjoyed sex, while 42 (28.4%) did not. Major barriers to sexual enjoyment were frequent misunderstandings 34 (80.9%, p = 00001); accommodation type (0.00001) and infidelity 29 (69.1%). The response probabilities showed that males (0.71 Nigeria, 0.73 abroad) enjoyed sex, compared to females (0.70 Nigeria, 0.72 abroad).Overall, this study showed significant improvement in sexual enjoyment/intimacy among respondents. However, misunderstanding and accommodation type were statistically significantly associated with sexual enjoyment. In the face of rising global uncertainties/economic downturn, regular pleasurable sex is advocated among married couples, particularly females, in order to maintain physical, mental and psychological wellbeing